2008
DOI: 10.1002/adsc.200800329
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Reusable Polyaniline‐Supported Palladium Catalysts for Open‐Air Oxidative Heck Reactions under Base‐ and Ligand‐Free Conditions

Abstract: Oxidative Heck reactions of arylboronic acids and alkenes are carried out in the presence of polyaniline-supported palladium catalysts using air as a co-oxidant to afford the Heck products with excellent yields and selectivities under base-and ligand-free conditions. The catalyst was recovered by simple filtration and used for several cycles with consistent activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 34 publications
4
28
3
1
Order By: Relevance
“…In continuation of our studies on the applications of environmentally benign catalysts for the development of useful new synthetic methodologies with PANI, [18] we focused our attention on the preparation of porous Fe 3 O 4 nanoparticles encaged in mesoporouspolyaniline microspheres, Fe 3 O 4 @mPANI, its characterization and its catalytic application in the synthesis of diaryl ethers from aryl chlorides and phenols. The thermal and chemical stability of Fe 3 O 4 @mPANI could enable activation of the C À Cl bond of aryl chlorides in the cross-coupling without deforming or aggregating the Fe 3 O 4 nanoparticles, which was not possible with bare magnetic Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our studies on the applications of environmentally benign catalysts for the development of useful new synthetic methodologies with PANI, [18] we focused our attention on the preparation of porous Fe 3 O 4 nanoparticles encaged in mesoporouspolyaniline microspheres, Fe 3 O 4 @mPANI, its characterization and its catalytic application in the synthesis of diaryl ethers from aryl chlorides and phenols. The thermal and chemical stability of Fe 3 O 4 @mPANI could enable activation of the C À Cl bond of aryl chlorides in the cross-coupling without deforming or aggregating the Fe 3 O 4 nanoparticles, which was not possible with bare magnetic Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[41,42] We found that not all Pd 2 + was converted to Pd + and unreacted Pd 2 + species could coordinate with chain 'N' of the polymer. [43] XPS analysis indicates that 1.64 wt % of palladium was present on the surface of the polymer matrix. TEM analysis failed to reveal any evidence of the formation of metallic palladium in the sample.…”
mentioning
confidence: 99%
“…Stabiliziranje katalizatora ligandima je omogućilo smanjenje korištenja katalizatora sve do 1 % u poređenju sa 10 ili 20 % koliko je korišteno u prethodnim slučajevima. Kompleks formiran između Pd(OAc) 2 i 2,9-dimetil-1,10-fenantrolina (DmPhen) je mogao katalizirati reakciju alkena sa različitim supstituiranim arilbornim kiselinama u izvrsnom iskorištenju (9,10). Kakogod, kada su korišteni supstrati kao što je 2-cikloheksenon i sterički nepovoljna borna kiselina, DmPhen-Pd-kompleks formira sporedne produkte kao što su homokuplovani produkti i fenoli, smanjujući prinos produkta.…”
Section: Uvodunclassified